Backlash Against Rights Advocacy (Discourse of Law and Administration, 2026)
Movements targeting fundamental rights increasingly resort to instruments and remedies designed to protect such rights (in this chapter we refer to these as the “rights-based” instruments): strategic lawsuits, freedom of expression, non-governmental organizations, citizens’ initiative etc. They abuse democratic (rights-based) mechanisms for anti-democratic purposes. In responding to this challenge democratic actors and institutions must carefully balance, on one hand, the need to actively (“militantly”) protect human rights and the instruments which can be employed for that purpose, and, on the other hand, the necessity of avoiding abuses and shortcomings which may occur. Such a balancing can take different forms in various social, cultural, and religious contexts. These issues, with particular attention paid to freedom of expression, are addressed in this chapter.
Keywords: freedom of expression; First Amendment; hate speech; fighting words; SLAPP